Analysis of Factors Associated with the Incidence of Chronic Energy Deficiency (CED) Among Pregnant Women at the Tapos Community Health Center (Uptd Puskesmas) in Depok From January to May 2026 - Sugiharti Sugiharti; Muninggar Muninggar; Fabit Mulyati Anur; Sintia Lusiana (Gayaku Publisher, 2026)
Background: In pregnant women, nutritional status is an important indicator in determining health status. Insufficient energy and protein intake in pregnant women can cause Chronic Energy Deficiency (CED). Objective: To determine the factors related to chronic energy deficiency (CED) in pregnant women at the UPTD Tapos Depok Health Center for the period January-May 2026. Method: This research design uses a quantitative research method with cross-sectional methodology, the sample size is 83 respondents. Results: There is a relationship between maternal age and the incidence of CED with a P value of 0.000, There is a relationship between parity and the incidence of chronic energy deficiency with a P value of 0.000, There is no relationship between income and the incidence of chronic energy deficiency with a P value of 0.090, There is a relationship between knowledge and the incidence of chronic energy deficiency with a P value of 0.031. Conclusion: The conclusion of the four variables in this study is that three of them are related to the incidence of chronic energy deficiency and one is not related.